HOW BRAND IMAGE AND AUGMENTED REALITY AFFECT PURCHASE DECISIONS IN ONLINE MARKETPLACE - Michaela, Rachel; Selamat, Frangky (International Journal of Application on Economics and Business, 2025)
This study aims to examine the influence of brand image and augmented reality on purchase decisions, with brand trust serving as a mediator. The research population includes consumers who have previously purchased Maybelline products through Shopee in DKI Jakarta. A total of 165 respondents were selected as samples, with criteria including age, residency, prior experience purchasing Maybelline products, and an interest in beauty trends. This research utilized purposive sampling using a descriptive method to collect respondent data through an online Google Forms questionnaire distributed via social media. The collected data was then thoroughly examined and analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS4 software. The results indicate that brand image has a positive and significant effect on purchase decisions, and with brand trust playing a partial mediating role between brand image and purchase decisions. Furthermore, augmented reality does not have a positive or significant effect on purchase decisions; however, brand trust plays a partial mediating role between augmented reality and purchase decisions. In addition to contributing to practical implication, this research is anticipated to provide meaningful insights for Maybelline products sold on Shopee to better understand the concepts of brand image and brand trust, as well as the application of augmented reality, in order to enhance purchase decisions.